2016
DOI: 10.1016/j.nbd.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DJ-1 impairs antioxidant response by altered glutamine and serine metabolism

Abstract: The oncogene DJ-1 has been originally identified as a suppressor of PTEN. Further on, loss-of-function mutations have been described as a causative factor in Parkinson's disease (PD). DJ-1 has an important function in cellular antioxidant responses, but its role in central metabolism of neurons is still elusive. We applied stable isotope assisted metabolic profiling to investigate the effect of a functional loss of DJ-1 and show that DJ-1 deficient neuronal cells exhibit decreased glutamine influx and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 77 publications
2
30
0
2
Order By: Relevance
“…In a recent study by our lab, we investigated the role of DJ-1 on cellular metabolism in post-mitotic human neurons derived from the midbrain [3]. In line with the common observation of increased sensitivity to ROS, we observed an increased GSSG (oxidised glutathione) to GSH (reduced glutathione) ratio and increased sensitivity to the ROS inducing compound 6-hydroxydopamine, an oxidation product of dopamine.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In a recent study by our lab, we investigated the role of DJ-1 on cellular metabolism in post-mitotic human neurons derived from the midbrain [3]. In line with the common observation of increased sensitivity to ROS, we observed an increased GSSG (oxidised glutathione) to GSH (reduced glutathione) ratio and increased sensitivity to the ROS inducing compound 6-hydroxydopamine, an oxidation product of dopamine.…”
supporting
confidence: 57%
“…Upon elevated, but non-apoptotic oxidative stress the SSP, transsulfuration pathway and 1C metabolism was up regulated and centrally controlled by ATF4. Concluding from our finding that loss of DJ-1 affects serine and 1C metabolism, that loss of DJ-1 makes cells more susceptible to oxidative stress [3] and that neuronal cells exposed to oxidative stress induce ATF4 to increase serine biosynthesis, transsulfuration and 1C metabolism [6], is suggestive that DJ-1 might control these metabolic pathways via ATF4 (Figure 1). However, this is still under investigation.…”
mentioning
confidence: 97%
“…Vor diesem Hintergrund und der weiterhin kontroversen Debatte über den potenziell neuroprotektiven Effekt der MAO-B-Inhibitoren erfolgt der Einsatz in der Therapie des IPS entweder zur frühen symptomatischen Behandlung (Selegilin, Rasagilin) oder ausschließlich als Add-on-Therapie beim Auftreten motorischer Fluktuationen (Safinamid). Die Diskussion über die Entstehung des Parkinson-Syndroms ist durch die jüngsten Ergebnisse genetischer Untersuchungen zur Bedeutung der Mitochondrien erneut aufgeflammt [45]. Die Bedeutung von oxidativem Stress und, damit verknüpft, der Rolle der MAO ist weiterhin Gegenstand der wissenschaftlichen Diskussion [46].…”
Section: Mao-b-inhibitorenunclassified
“…Moreover, Meiser et al. demonstrated that loss of PARK7 decreases serine biosynthesis and glutamine influx, two pathways that provide precursors for de novo synthesis of glutathione, an important antioxidant . In this regard, PARK7 levels were decreased in the hippocampus of adolescent Wistar rats treated with ∆9‐THC .…”
Section: Schizophrenia and Endocannabinoid Systemmentioning
confidence: 99%